2021
DOI: 10.1002/ghg.2054
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between economic growth, renewable and nonrenewable energy use and CO2 emissions: empirical evidences for Brazil

Abstract: This article examined the causal relationship between economic growth, carbon dioxide (CO2), and renewable and nonrenewable energy use for the 27 Brazilian states from 1997 to 2016. In order to achieve this objective, the system‐generalized method of moment was applied together with the autoregressive vector model for panel data. Estimates of the multivariate model established important relationships to promote public policies. Empirical results show that there is a two‐way relationship between economic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
2
4
1
Order By: Relevance
“…The surge in renewable energy by 1% will decrease the level of load capacity factor by 0.177% in the long term. This outcome does not correspond with the findings of Alola et al (2021) and Amarante et al (2021), who reported that renewable energy can help to achieve a sustainable environment in China and Brazil. Also, reported a positive association between load capacity factor and renewable energy consumption in the United States.…”
Section: Empirical Findingscontrasting
confidence: 97%
“…The surge in renewable energy by 1% will decrease the level of load capacity factor by 0.177% in the long term. This outcome does not correspond with the findings of Alola et al (2021) and Amarante et al (2021), who reported that renewable energy can help to achieve a sustainable environment in China and Brazil. Also, reported a positive association between load capacity factor and renewable energy consumption in the United States.…”
Section: Empirical Findingscontrasting
confidence: 97%
“…According to claims, GDP has a negative coefficient and has both short- and long-term effects on CO2 emissions ; this implies that if GDP rises by 1%, CO2 emissions decrease by 0.779 percent and 1.720 percent, respectively. This result is similar to Amarante et al (2021) , Al-mulali et al (2016) , Ahmed (2020) , Akif and Asumadu (2019) , Prince and Okechukwu (2019) , Liu et al (2020) , Voumik et al (2022b) and Vo and Vo (2019) and the result is contradicted to Ozgur et al (2022) , Safi et al (2021) , Tao et al (2021) , Acaravci and Ozturk (2010) , Ahmed et al (2020) , Aydin et al (2019) , Awais and Wang (2019) , Abbasi et al (2020) , Bano et al (2018) , Tauseef et al (2019) , Erdogan et al (2020) , Fakher (2019) , Marrero (2010) , and Liu et al (2020) . By contrast, the coefficient of is positive and significant statistically, which shows that if rises by 1 percent, then it increases emissions by 0.0124 percent.…”
Section: Resultssupporting
confidence: 88%
“…Renewable energy reduces CO2 emissions; that is, if renewable energy consumption increases by 1%, CO2 emissions are reduced by .1129 percent. This result is similar to Haldar and Sethi (2021) , Esquivias et al (2022) , Sahoo and Sethi (2021) , Amarante et al (2021) , Al-mulali et al (2016) , Erdogan et al (2020) , Marrero (2010) , Prince and Okechukwu (2019) , Liu et al (2020) , and Voumik et al (2022c) . Furthermore, the energy intensity coefficient value is .3953, which is both positive and significant, indicating that if energy intensity increases by 1%, CO2 emissions increase by .3953%.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Climate change and global warming may lead to a significant increase in heat-related mortality and morbidity in the future [ 5 ]. In this context, renewable energy appears to be a key aspect to improve the environment and health, but renewable energy also has a positive effect on economic growth and human development [ 6 , 7 ]. Based on these benefits, renewable energy plays an important role in a modern and responsible world consisting of healthy and prosperous countries.…”
Section: Introductionmentioning
confidence: 99%